Prevalence of HIV in Blood Donors - Tiwari, B R; Karki, S; Ghimire, P.; Yadav, P.; Rajkarnikar, M (Journal of Nepal Health Research Council, 2009)
Background: Nepal is categorized as a country with ‘concentrated' epidemic of HIV Nepal Red Cross Society, Blood Transfusion Service has implemented considerable efforts to supply the safe blood and blood products according to the increasing demand. A trend analysis might prove valuable to understand the outcome and appropriately plan for further improvements in providing safe blood supply. The study aimed to assess the trends of HIV seroprevalence over the six years in nationwide and in urbanized setting of Kathmandu Valley. Methods: This is a retrospective study conducted among Nepalese blood donors through the years 2001-2007. Serum samples were tested using third generation ELISA tests, strictly following the instructions of manufacturers. The donors' information was collected through the donor record register through the respective Blood Transfusion Services. Results: The overall seroprevalence of HIV among the total blood donors in nation wide and in Central Blood Transfusion Service (CBTS), Kathmandu through the six years of review (from 2001-2007) was 0.33% and 0.4% respectively. A significant decreasing trend in HIV seroprevalence was observed both in nationwide and in Central Blood Transfusion Service, Kathmandu (P< 0.001). Conclusion: The analysis of trends in HIV seroprevalence among blood donors through the year 2001- 2007 showed a significantly decreasing trend, probably due to the cumulative effect of increasing awareness of HIV and improved screening system for safe blood donation. However, an abrupt increase in demand of blood supply was associated with significant increase in seroprevalence in the year 2005/2006. Key words: Nepalese blood donors; Seroprevalence; Trends. doi: 10.3126/jnhrc.v6i2.2203 Journal of Nepal Health Research Council 2008 Oct;6(13): Page: 93-97